TAC3 Gene Products Regulate Brain and Digestive System Gene Expression in the Spotted Sea Bass (Lateolabrax maculatus) - Zhang, Zhanxiong; Wen, Haishen; Li, Yun; Li, Qing; Li, Wenjuan; Zhou, Yangyang; Wang, Lingyu; Liu, Yang; Lyu, Likang; Qi, Xin (Frontiers in Endocrinology, 2019)
Neurokinin B (NKB) is a member of the tachykinin (TAC) family that plays important roles in mammalian growth by modulating prolactin (PRL) synthesis and secretion and causing contraction of the stomach and intestine. However, its potential molecular mechanisms in teleosts are less clear. The aim of this study was to explore the role of NKB in fish growth using the spotted sea bass (Lateolabrax maculatus) as a model. In the present study, two TAC3 and two TACR3 genes were identified in the spotted sea bass. Sequence analysis showed that two transcripts, TAC3a and TAC3b, encode several NKBs: NKBa-13, NKBa-10, NKBb-13, and NKBb-10. Expression analysis in different tissues revealed that TAC3 and TACR3 are mainly expressed in the brain, stomach and intestine of the spotted sea bass. In situ hybridization indicated that the TAC3a and TAC3b mRNAs are both localized in several regions of the brain, such as the telencephalon and hypothalamus, and that TACR3a and TACR3b are localized in the intestinal villus and gastric gland. To investigate the potential role of NKBs in regulating growth, in vitro experiments were performed to detect the effect of NKBs on the expression of growth-related genes in the brain and brain-gut peptide (BGP)-related genes in the stomach and intestine. NKBb-13 was the most critical ligand in regulating the expression of growth-related genes in the brain and brain-gut peptide (BGP)-related genes in the stomach. The expression of cholecystokinin (cck) was enhanced by NKBa-13, NKBa-10, and NKBb-10 but not NKBb-13 in the intestine. These results indicated that NKBs play a role in the growth of spotted sea bass.